Career Readiness Program: Soft Skill dan Edukasi Keuangan bagi Siswa SMK 3 Karawang - Arina Hidayati; Triyono, Triyono; Tabah Rizki; Fitri Rasdayanti; Edward Kurniawan Saputra Letsoin; Wiwin Lestari (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The implementation of community service in SMK N 3 Karawang was carried out by teachers from Horizon University Indonesia. SMK N 3 Karawang is one of the private secondary schools located in Kondangjaya area, East Karawang, Karawang City. Initial observations showed that career planning education is needed especially for vocational high school students. For this reason, the author strengthens as part of the academic world to help prepare students' careers, so that in the future it is hoped that the needs of the business world will successfully absorb labor from SMK graduates. This community service activity (PKM) is carried out with a continuous socialization method. There are two types of delivery methods, namely, lectures and discussions based on student center learning. Both the lecturer and the community service team give priority to hands-on activities for students. Thus, PKM participants not only understand in theory, but also understand the application in the industrial business world in the future.